2011
DOI: 10.2527/jas.2010-3288
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomics of the muscle response to restraint and transport in chickens1

Abstract: In the present study, we used global approaches (proteomics, transcriptomics, and metabolomics) to assess the molecular basis of the muscle response to stress in chickens. A restraint test, combined with transport for 2 h (RT test) was chosen as the potentially stressful situation. Chickens (6 wk old) were either nontreated (control chickens) or submitted to the RT test (treated chickens). The RT test induced a 6-fold increase in corticosterone concentrations, suggesting hypothalamic-pituitary-adrenal axis act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 68 publications
(66 reference statements)
1
17
0
Order By: Relevance
“…The authors reported few overlaps between the proteomic and transcriptomic analyses. Such results were consistent with other studies using both approaches [28,29]. The use of pathway analysis by combining the two levels of gene expression helps to better understand the physiological differences between breeds.…”
Section: Comparison Of Breedssupporting
confidence: 93%
“…The authors reported few overlaps between the proteomic and transcriptomic analyses. Such results were consistent with other studies using both approaches [28,29]. The use of pathway analysis by combining the two levels of gene expression helps to better understand the physiological differences between breeds.…”
Section: Comparison Of Breedssupporting
confidence: 93%
“…The derangement of postmortem alteration such as those that drive to pale soft exudative meats can also be analysed by proteomics (Molette et al , 2003 ). Given the background of the growing sensitivity of consumers and of policy makers on animal welfare, future applications of proteomics for the identification of biomarkers of stress and welfare after transport, for example, or preslaughtering procedures, are also envisaged (Hazard et al , 2011 ).…”
Section: Proteomics In Animal Products Post Harvestmentioning
confidence: 99%
“…On the other hand, there are few reports in the literature on the effects of transportation on muscle tissue protein expression. Among them, Hazard et al [16] used proteomic, transcriptomic, and metabolomic approaches to assess the molecular basis for muscle response to stress in chickens, reporting expression changes in 45 protein spots, found related mainly to the cytoskeletal structure or carbohydrate metabolism networks.…”
Section: Introductionmentioning
confidence: 99%